DETERMINATION ANTIOXIDANT ACTIVITY, TOTAL PHENOLICS, FLAVONOIDS CONTENT, OF JUNGRAHAB LEAVES (Baeckea frutescens L.) - Wahyu Priyo Legowo; Irma Erika Herawati; Lisna Dewi (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Medicinal plants are widely used to treat various diseases, and one of the reasons for this is the safety of medicinal plants. The active compounds in medicinal plants include phenolics and flavonoids, which are known to have antioxidant activity. Antioxidants play an essential role in the body's defense against various diseases because they prevent the negative effects of free radicals. Jungrahab (Baeckea frutescens L.) is a medicinal plant containing phenolics and flavonoids. This study aimed to determine the antioxidant activity of jungrahab leaf extracts using the 2, 2-diphenyl-1-picrylhydrazyl (DPPH) method. The results showed the antioxidant activity of the extract, water fraction, ethyl acetate, and n-hexane of jungrahab leaves with IC50 values of 12.62, 61.74, 60.66, and 63.99 ppm, respectively. Meanwhile, jungrahab extract has a total phenolic content of 52.40 mg GAE (Gallic Acid Equivalent)/g and a flavonoid content of 56.72 mg QE (Quercetin Equivalent)/g. Jungrahab extract showed strongest antioxidant category compared to its fractions. Keywords: phenolics content, flavonoids content, antioxidant activity, DPPH, jungrahab